Edukasi Pencegahan Aktivitas Judi Online - Thresia Hilda M.Y. Krey; Winna A.A. Senandi (LPPM Uncen, 2026)
Nowadays, online gambling in Indonesia has become a national emergency, claiming millions of victims (especially the poor) and generating hundreds of trillions in revenue, leading to fatal dependency, poverty, and even criminal activity. Easy access and aggressive advertising fuel addiction, leading to household economic ruin, increased online loan debt, and fueling crime and family conflict. This activity aims to provide the public with an understanding of the dangers of online gambling, including its types, dangers and negative impacts, and the various legal sanctions that threaten online gambling app users. The method used in this legal education activity was a lecture with material presentation and discussion with participants. Participants demonstrated their enthusiasm during the legal education activity by providing positive feedback and reactions. This demonstrated their understanding of the material presented regarding the dangers of online gambling. Online gambling requires vigilance because it is a dangerous activity that can destroy individuals, families, and communities by causing addiction, financial problems, and mental health disorders. Online gamblers and bookies can be subject to legal sanctions in accordance with statutory regulations.